Molecular basis for prostaglandin production in hosts and parasites - Kubata, B.K.; Duszenko, M.; Martin, K.S.; Urade, Y. (Elsevier, 2007)
Prostaglandins (PGs) comprise a family of structurally related bioactive lipid mediators that are involved in various symptoms associated with parasitic diseases. The molecular mechanisms of PG biosynthesis in animals have been studied extensively. Currently, several lines of evidence link their production with parasites. In this review we discuss the roles of PGs in parasite pathogenesis and physiology and the recent advances in our understanding of the enzymology of PG production in various parasites.